Dynamic Response of Economic Growth to Financial Development and Information and Communication Technology in Sub-Saharan Africa Countries - Olabisi, Olabode Eric (Issues in Social Science, 2024)
The aims of this research work are to test the dynamic response of economic growth to financial development and information and communication technology (ICT), and to investigate whether the interaction of financial development with better ICT infrastructure can promote economic growth. Growth theories predict that financial development and ICT positively influence economic growth, but the results are mixed. Therefore, the current study examines the dynamic response of economic growth to financial development and information and communication technology (ICT) for eight selected sub-Saharan African (SSA) countries covering 2000–2021. Applying pooled mean groups and mean group estimators, the findings reveal that ICT enhances growth in SSA, but financial development is otherwise. The result further shows that with the interaction of ICT with financial development, economic growth is positively influenced. Since the region is still undergoing development, it is suggested that there should be more investment in the ICT infrastructure.